Prelude to practical theology: variations on theory and practice - Stevenson-Moessner, Jeanne (Abingdon Press, 2008)
Stanza one: warming up -- Stanza two: variations on a theme -- Stanza three: movements -- Stanza four: discordant notes -- Stanza five: symphonic sound -- Stanza six: encore -- Curtain calls: acknowledgments